In Vivo ETosis of Human Eosinophils: The Ultrastructural Signature Captured by TEM in Eosinophilic Diseases - Neves, Vitor H.; Palazzi, Cinthia; Bonjour, Kennedy; Ueki, Shigeharu; Weller, Peter F.; Melo, Rossana C. N. (Frontiers in Immunology, 2022)
Eosinophilic diseases, also termed eosinophil-associated diseases (EADs), are characterized by eosinophil-rich inflammatory infiltrates and extensive eosinophil degranulation with clinically relevant organ pathology. Recent evidence shows that eosinophil cytolytic degranulation, that is, the release of intact, membrane-delimited granules that arises from the eosinophil cytolysis, occurs mainly through ETosis, meaning death with a cytolytic profile and extrusion of nucleus-originated DNA extracellular traps (ETs). The ultrastructural features of eosinophil ETosis (EETosis) have been studied mostly in vitro after stimulation, but are still poorly understood in vivo. Here, we investigated in detail, by transmission electron microscopy (TEM), the ultrastructure of EETosis in selected human EADs affecting several tissues/organ systems. Biopsies of patients diagnosed with eosinophilic chronic rhinosinusitis/ECRS (frontal sinus), ulcerative colitis/UC (intestine), and hypereosinophilic syndrome/HES (skin) were processed for conventional TEM. First, we found that a large proportion of tissue-infiltrated eosinophils in all diseases ( 45-65% of all eosinophils) were undergoing cytolysis with the release of free extracellular granules (FEGs). Second, we compared the morphology of tissue inflammatory eosinophils with that shown by in vitro ETosis-stimulated eosinophils. By applying single-cell imaging analysis, we sought typical early and late EETosis events: chromatin decondensation; nuclear delobulation and rounding; expanded nuclear area; nuclear envelope alterations; and extracellular decondensed chromatin spread as ETs. We detected that 53% (ECRS), 37% (UC), and 82% (HES) of all tissue cytolytic eosinophils had ultrastructural features of ETosis in different degrees. Eosinophils in early ETosis significantly increased their nuclear area compared to non-cytolytic eosinophils due to excessive chromatin decondensation and expansion observed before nuclear envelope disruption. ETosis led not only to the deposition of intact granules but also to the release of eosinophil sombrero vesicles/(EoSVs) and Charcot-Leyden crystals (CLCs). Free intact EoSVs and CLCs were associated with FEGs and extracellular DNA nets. Interestingly, not all cytolytic eosinophils in the same microenvironment exhibited the ultrastructure of ETosis, thus indicating that different populations of eosinophils might be selectively activated into this pathway. Altogether, our findings captured an ultrastructural signature of EETosis in vivo in prototypic EADs highlighting the importance of this event as a form of eosinophil degranulation and release of inflammatory markers (EoSVs and CLCs).